Assessing Farmers’ Awareness of Climate Change Impact: A Case of the Bundelkhand Region, India - -, Deepak Kumar Pathak; Gupta, Brijesh Kumar; -, A. P. Verma; -, Gaurav Shukla; -, Abhishek Kalia; -, Dheeraj Mishra; -, Pnkaj K Ojha; -, B.P.Mishra (Indian Journal of Extension Education, 2024)
The study was conducted in 2023-24 in the Bundelkhand region, India and examined the awareness of climate variability and its impacts on farmers. Analytical and descriptive research design was used in the present study. The present study was carried out in two districts namely, Jalaun and Datia of Bundelkhand. Four blocks were selected randomly from these districts, and a total of 320 respondents were selected randomly. The results revealed that most of the respondents were well informed about changes in crop cycles (81.87%), new pests and diseases (63.12%) and natural hazards like earthquakes and cyclones (69.06%). There are still considerable gaps in their knowledge of topics like biodiversity loss and groundwater depletion. Factor analysis revealed four principal components influencing awareness; natural hazards (.717), soil productivity (.681), pest and disease emergence (.775) excess water in surface (.818), and decline in groundwater level (.738). Correlation and regression analysis indicate that education, landholding, socio-economic status, information-seeking behaviour, economic motivation and scientific orientations are significantly and positively associated with climate change awareness. The findings suggest that focused awareness efforts need to be made that utilize media and extension advisory services to improve farmers’ awareness and ability to adapt.